The Effect of Multiple Intelligences and Learning Motivation on Social Studies Learning Achievement of Grade V Elementary School Students - Muh. Fahrul; Idawati Idawati; Muhammad Nawir (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to find out how the influence of multiple intelligences on social studies learning achievement in Class V Elementary School; the effect of learning motivation on social studies learning achievement in Class V Elementary School; and the effect of multiple intelligences and learning motivation on social studies learning achievement in Class V of Elementary School in Rappocini District. This type of research is expost-facto research, the method used is quantitative descriptive method with the aim of being able to provide an overview of the problem to be studied. The sample in this study is part of the population with the sampling technique is proportional stratified random sampling. The data collection method used was a multiple intelligences questionnaire, a motivational questionnaire and documentation of student achievement. The data analysis technique used is first by using a descriptive statistical approach, inferential statistical tests, and simple linear regression tests. The results of the study, 1) the effect of multiple intelligences on students with an average of 80.12 in the medium category or having an influence on student achievement in class V 2) the effect of student motivation in the medium category means that student learning motivation has an influence on student achievement; 3) based on a simple linear regression test with the results of the study that the X variable has a significant effect on the Y variable. From the test results above it is proven that there is a significant influence between multiple intelligences and learning motivation on social studies learning achievement in fifth grade students in the Rappocini sub-district, Makassar City